Penggunaaan M-Banking BRImo Terhadap Kemudahan Transaksi Perbankan Nasabah Bank BRI di Kota Medan - Hasyim; Devima , Hotma Boru Hutahaean; Situmorang, Romasi; Devima, Santia (CV. Lenggogeni Data Publishing, 2023)
Services that have been designed to provide attractive and comfortable, safe and simple services for customers, with the ongoing development of information technology that has created new types of business and opportunities and increased business transactions carried out through electronic processes. The evolution of technology in the banking sector allows every individual to transfer money, buy and sell, and additional transactions, so with services it is possible to provide comfort and mobility for bank customers to carry out work and needs in their daily lives. One type of service offered by BRI bank is BRImo which aims to make it easier for customers to make transactions without visiting the bank because customers are busy with lots of activities so they can be anywhere and still be able to make transactions and avoid any disruption to their activities. This research uses a qualitative research method where qualitative research is a commonly used scientific method and is carried out by a group of researchers in the field of social sciences, including scientific education.